Controlled dc Monitoring of a Superconducting Qubit - Kringhøj, A.; Wadum Larsen, Thorvald; van Heck, Bernard; Sabonis, D.; Erlandsson, O.; Petkovic, Ivana; Pikulin, Dmitry; Krogstrup, Peter; Petersson, Karl; Marcus, Charles (Physical Review Letters, 2020)
Creating a transmon qubit using semiconductor-superconductor hybrid materials not only provides electrostatic control of the qubit frequency, it also allows parts of the circuit to be electrically connected and disconnected in situ by operating a semiconductor region of the device as a field-effect transistor. Here, we exploit this feature to compare in the same device characteristics of the qubit, such as frequency and relaxation time, with related transport properties such as critical supercurrent and normal-state resistance. Gradually opening the field-effect transistor to the monitoring circuit allows the influence of weak-to-strong dc monitoring of a "live" qubit to be measured. A model of this influence yields excellent agreement with experiment, demonstrating a relaxation rate mediated by a gate-controlled environmental coupling.